Malay Speech Intelligibility Test (MSIT) for Deaf Malaysian Children - Yusof, Zulkhairi Md.; Hussain, Ramlah; Ahmed, Mohiuddin (International Journal of Integrated Engineering, 2014)
This paper presents a novel approach to objectively measure speech intelligibility of deaf Malaysian children using nonsense syllables as test words. In this study, speech intelligibility of deaf children is measured through the ability to say simple syllables (consisting of a consonant and a vowel) for all the 22 Malay consonants. The MSIT score should indicate how well these children can produce speech; the higher the score, the better their speech intelligibility. The MSIT have been tested with twenty deaf and ten normal hearning Malaysian children and has been verified by five naïve and two expert listeners. The application of the test is presented as speech intelligibility index for deaf children in a deaf school. The successful development of the MSIT system serves to assist speech pathologist, therapist, teachers and parents of deaf children to determine the level of Malay speech deficiencies and the effectiveness of corrective measures taken.